2017
DOI: 10.3390/rs9090920
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Low-Level Clouds and Fog Modify the Diurnal Cycle of Orographic Precipitation Using In Situ and Satellite Observations

Abstract: Satellite orographic precipitation estimates exhibit large errors with space-time structure tied to landform. Observations in the Southern Appalachian Mountains (SAM) suggest that low-level clouds and fog (LLCF) amplify mid-day rainfall via seeder-feeder interactions (SFI) at both high and low elevations. Here, a rainfall microphysics model constrained by fog observations was used first to reveal that fast SFI (2-5 min time-scales) modify the rain drop size distributions by increasing coalescence efficiency am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…Barros et al (2018) showed that model simulations using aerosol activation spectra from local sources and activation spectra from remote aerosol sources resulted in a significant spatial and temporal redistribution of precipitation in the central Himalayas, including changes in cloud dynamics and the vertical distribution of hydrometeors. The latter is the basis for remote sensing measurements of precipitation, and therefore understanding how ACIs modify precipitation structure is key to improving retrievals in mountainous regions (e.g., Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Barros et al (2018) showed that model simulations using aerosol activation spectra from local sources and activation spectra from remote aerosol sources resulted in a significant spatial and temporal redistribution of precipitation in the central Himalayas, including changes in cloud dynamics and the vertical distribution of hydrometeors. The latter is the basis for remote sensing measurements of precipitation, and therefore understanding how ACIs modify precipitation structure is key to improving retrievals in mountainous regions (e.g., Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, [25] showed how IGP aerosol can remain sequestered to form pools over low lying areas and valleys in the Middle Himalaya after there is a full retreat of the pollution over the IGP. The aerosol pool is eventually scavenged by the formation of low-level clouds and fog, and washed out by rainfall similar to subregional scale forcing in the inner region of the Southern Appalachians investigated by [21,22]. Specifically, [26] showed that, in the presence of regional scale aerosol clouds and during dry periods, the mean volume aerosol concentration increased, and so did the aerosol mass concentrations in two different valleys of Central Nepal, the Marshyangdi and the Kathmandu, followed by rain-out.…”
Section: Introductionmentioning
confidence: 89%
“…Intercomparison modeling studies using CN with different activation characteristics suggest that the timing and intensity of precipitation are tightly linked to regional and subregional scale aerosol characteristics. Recent NWP (Numerical Weather Prediction) simulations in the Southern Appalachians Mountains (complex terrain with moderate elevation <2500 m) show that using regional CCN activation characteristics obtained from field measurements [20] has strong impact on rainfall structure as compared to standard continental aerosol by reducing unrealistic light rainfall on the one hand, and by intensifying convection on the other due to strong modification of cloud microphysics, even more so in the case of local vis-a-vis synoptic forcing [21,22]. This begs the question of whether the characterization of regional aerosol is not only desirable, but indeed necessary toward achieving a substantial improvement in NWP's predictive skill at high spatial resolution and short time-scales (< 24 hr) toward decreasing phase errors in storm arrival and improving rainfall intensity [2,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A high-density high-elevation network of rain gauges has been operating for 15 years in this region. Previous research using ground observations (Prat & Barros, 2007;Wilson & Barros, 2014;Duan & Barros, 2017;Miller et al, 2019) elucidated the dominant precipitation regimes in the SAM. The Cataloochee Creek Basin (CCB, 128 km 2 ), a USGS (United States Geological Survey) benchmark watershed, is selected for the end-to-end demonstration due to the high quality of streamflow observations (Figure 2), and nearby catchments are used to explore model transferability.…”
Section: Study Areamentioning
confidence: 99%